اضطرابات النظم المشاهدة في احتشاء العضلة القلبية خلال اليومين الأوليين - أحمد, هدى (Latakia University Journal -Medical Sciences Series, 2014)
إن هدف البحث هو تقدير نسبة حدوث اضطرابات النظم خلال الـ 48 ساعة الأولى من احتشاء العضلة القلبية وتحديد نوعها وعلاقتها مع نمط الاحتشاء وموقعه سواء عند المرضى الذين طبق لهم علاج حال للخثرة أو الذين لم يطبق لديهم، وكذلك تحديد علاقتها مع نسبة الوفيات خلال فترة إقامة هؤلاء المرضى في العناية القلبية المشددة. بدأت الدراسة من 1 تشرين الأول 2012 واستمرت 12 شهراً حتى 1 تشرين الأول 2013، تكونت عينة الدراسة من /187/ مريضاً قبلوا في قسم العناية القلبية بحالة احتشاء عضلة قلبية حاد، منهم (142) مريضاً (76%) كانوا ذكوراً، و(45%) مريضاً (24%) كانوا إناثاً. بينت الدراسة أن: * 107 مريض (57%) من مرضى الدراسة كانوا مدخنين، فالتدخين هو العامل الأهم من عوامل الخظورة للإصابة باحتشاء العضلة القلبية. * خوارج الانقباض البطنية هي أشيع اللأنظيمات الحاصلة خلال الـ 48 ساعة الأولى من احتشاء العضلة القلبية الحاد (79%) يليها النظم البطيني الذاتي المتسارع (43%). *ارتفاع نسبة حدوث اضطرابات الخطيرة مثل الـ VT و VF (9%) و(9%) لدى المجموعة التي لم يطبق لها الستربتوكيناز مقارنة مع المجموعة التي طبق لها (4.5%) و (3.8%) على الترتيب. *انخفاض الـ EF يزيد من احتمال حدوث اضطرابات نظم بطينية مهددة للحياة مثل الـ VT. *الإصابة بالداء السكري لا تزيد خطورة الإصابة باضطرابات النظم المراقبة في الدراسة. This research tries to the rate of arrhythmia manifested during the first (48) hours of heart infarction and define its nature as well as its relationship with heart infarction in regard to patients subjected to anti-coagulation (streptokinase) therapy and patients who were not subjected to it. Moreover, it also aims to detect the relationship between arrhythmia and the death rates of the patients during their stay in the Heart Intensive Care Unit. The study started in October 2012 and lasted twelve months, up to October 2013. The sample of study here consisted of (187) patients hospitalized in the Heart Intensive Care Unit having acute myocardial infarction. The sample included (142) males (76 % of the sample) and (45) females (24%). The research reached the following findings: A hundred and seven of the patients monitored in the study were smokers; and smoking was the most important risk factor causing myocardial infarction. Ventricular extra systole were the most common symptoms of acute myocardiac infarction arrhythmia during the first (48) hours of hospitalization reaching (79%). The second was increased auto ventricular rhythms rating (43 %). High rates of dangerous arrhythmia like (VT) and (VF) rating (9%) in patients who were not subjected to streptokinase (anti-coagulation) compared with those subjected to it (4. 5%), and (3.8) respectively. Decreased (EF) increased the possibility of life-threatening ventricular arrhythmia like (VT). Diabetes did not increase the dangers of arrhythmia monitored in this research.